Nonfatal injuries in Korean children and adolescents, 2007-2018 - Gyu Min Yeon; Yoo Rha Hong; Seom Gim Kong (The Korean Pediatric Society, 2022)
Background Injury is the leading cause of death or disability in children and adolescents. Rates of deaths from injuries have recently declined, but studies of the occurrence of nonfatal injuries are lacking. Purpose This study aimed to investigate nonfatal injuries in children and adolescents younger than 20 years based on data from the Korean National Health and Nutrition Survey, 2007-2018. Methods A questionnaire survey was conducted to determine whether children and adolescents had experienced an injury requiring a hospital visit in the previous year. We investigated each injury's risk factors and characteristics. Results Of a total of 21,598 children and adolescents, 1,748 (weighted percentage, 8.1%) experienced one or more injuries in the previous year. There was no yearly difference in the proportion of injuries experienced. Among the male subjects, 10.0% had an injury experience; among the female participants, 6.1% had an injury experience (P<0.001). The highest rate was 9.0% in children aged 1-4 years. In multivariate logistic regression analysis, male sex; having an urban residence; having restricted activity due to visual, hearing, or developmental impairment; and attention deficit/hyperactivity disorder were significant risk factors for injury experience. The characteristics of up to 3 injuries per patient were investigated, and 1,951 injuries were analyzed. Falls and slips accounted for 34.9%, collisions for 34.1%, and motor vehicle accidents for 11.3% of the total injuries. Ninety-six percent of injuries were unintentional, 20% caused school absences, and 10% required hospitalization. Conclusion Among Korean children and adolescents, 8.1% experienced injuries at least once a year with no significant differences in incidence over the past 12 years. Greater attention and effort to prevent injuries are needed.